Gamma-aminobutyric acid as an element of the mechanisms of cerebro-renal interactions - N.D. Filipets; D.D. Іvanov; О.V. Gerush; О.О. Filipets; О.Н. Kmet; N.M. Fundiur; K.V. Slobodian (Počki)
The presence of many common aspects in autoregulatory mechanisms and processes of ensuring the constancy of the internal environment determines the uniqueness of the cerebro-renal system. Gamma-aminobutyric acid (GABA), in addition to the key coordinating role in brain activity and its metabolism, has inherent regulatory effects in non-neuronal tissues. Given the fact that there is a relationship between GABA levels and the functional and metabolic state of other organs and systems, the aim of the work is to focus on scientific information regarding local GABAergic systems, the location of their components in the nephron and the renal effects of GABA under different conditions. In addition to the fact that GABA has therapeutic potential against acute kidney injury and chronic kidney disease, pharmacological modulators of GABA can provoke nephrotoxicity. The reasons for the diversity of renal responses under the influence of GABA and agents with agonist activity are multifactorial in nature, which should be taken into account, and within the framework of GABAergic strategies, effective and safe therapeutic approaches should be sought and applied.